COCOA PROCESSING INDUSTRY FEASIBILITY ANALYSIS (CASE STUDY IN HOUSE OF CHOCOLATE DEPARTMENT OF INDUSTRY CENTRAL SULAWESI PROVINCE) IN PALU - Evyana Marwati Bangkele; Made Antara; Lien Damayanti (AGROLAND: The Agricultural Sciences Journal, 2016)
This study aims to determine the appropriateness of the establishment of cocoa processing industry (Rumah Coklat Office of Industry and Trade of Central Sulawesi Province) in Palu     based on market aspects, technical aspects, aspects of the organization and management as well as financial aspects. The research was conducted in the city of Palu, namely Rumah    Coklat Industry and Trade Office of Central Sulawesi province were carried out from July to September 2016. The method used was survey used data sourced from Rumah Coklat Department of Industry and Trade of Central Sulawesi province and institutions associated with the study and the results of research conducted by the Center for R & D relating to the cacao processing. Data collected was processed and analyzed the aspects of the market, technical, organizational and management aspects and financial aspects. The results showed that the business of processing cocoa into chocolate and chocolate converture liqour from the aspect of the market is feasible to set up because it has a fairly large market opportunities, both domestic market and overseas markets. Based on a technical aspect, the business of processing cocoa into chocolate liqour and chocolate converture feasible to implement in Palu because of the availability of raw materials, labor, buildings and facilities equipment, the need for production machinery and equipment, the capacity of production capacity and the production process is relatively easy to be fulfilled and realized. Based on the aspect of organization and management, processing of chocolate is feasible. Because the needs of the labor management section and production section is obtained in accordance with the wishes of the company, as well as the maintenance of legality companies easily obtained. Financial aspects of the analysis results obtained by period of return on investment or payback period is 7 years. NPV is Rp. 182,141,428. IRR is about 14 and PI is 1.08%.  BEP amounted to 58.28% of total sales or Rp.  323,561,529. as well as the results of the sensitivity analysis shows that this cocoa processing business into chocolate liquor and converture very sensitive to the price of raw materials cocoa and the amount of the sale. Based on the calculation and analysis can be concluded that the cocoa processing industry namely Rumah Coklat Office of Industry and Trade of the Province of Central Sulawesi in Palu meet the eligibility criteria and eligible to be run the business.